Estimation of large domain Al foam permeability by Finite Difference methods (2013)
Classical methods to calculate permeability of porous media have been proposed mainly for high density (e.g. granular) materials -- These methods present shortcomings in high porosity, i.e. high permeability media (e.g. metallic foams) -- While for dense materials permeability seems to be a function of bulk properties and occupancy averaged over the volume, for highly porous materials these parameters fail to predict it -- Several authors have attacked the problem by solving the Navier-Stokes equations for the pressure and velocity of a liquid flowing through a small domain (Ωs) of aluminium foam and by comparing the numerical results with experimental values (prediction error approx. 9%) -- In this article, we present calculations for much larger domains (ΩL) using the Finite Difference (FD) method, solving also for the pressure and velocity of a viscous liquid flowing through the Packed Spheres scenario -- The ratio Vol(ΩL)/Vol(Ωs) is around 103 -- The comparison of our results with the Packed Spheres example yields a prediction error of 5% for the intrinsic permeability -- Additionally, numerical permeability calculations have been performed for Al foam samples -- Our geometric modelling of the porous domain stems from 3D X-ray tomography, yielding voxel information, which is particularly appropriate for FD -- Ongoing work concerns the reduction in computing times of the FD method, consideration of other materials and fluids, and comparison with experimental data